Impact of National Drug Pricing Policy 2018 on access to medicines in Lahore division, Pakistan: a pre-post survey study using WHO/HAI methodology. Issue 10 (8th October 2020) - Saeed, Amna; Saeed, Hamid; Saleem, Zikria; Yang, Caijun; Jiang, Minghuan; Zhao, Mingyue; Ji, Wenjing; Aziz, Muhammad Majid; Khan, Faiz Ullah; Gillani, Ali Hassan; Atif, Naveel; Fang, Yu; et al.
Abstract : Objective: To evaluate the impact of new National Drug Pricing Policy (NDPP) 2018 on access to medicines in terms of prices, availability and affordability. Design: Two cross-sectional surveys were undertaken before and after the launch of NDPP 2018, using a modified WHO/Health Action International (WHO/HAI) methodology. Setting: Four districts of Lahore division, Pakistan. Participants: 16 public sector hospitals and 16 private sector retail pharmacies. Measures: The pre and post survey data on prices and availability of lowest price generics (LPGs) and originator brands (OBs) of 50 medicines were obtained by visiting the same public and private sector health facilities (n=32). Out of 50, 46 surveyed medicines were from the National Essential Medicines List. Inflation-adjusted median unit prices (MUPs) and median price ratios (MPRs) from 2019 were used for price comparison. Affordability was calculated in terms of number of days' wages required to get a standard treatment by the lowest paid unskilled government worker. Results: The overall mean percent availabilities remained poor in both years, that is, far less than 80%. In the public sector, the mean percent availability of OBs improved from 6.8% to 33.1%, whereas, in the case of LPGs, it was reduced from 35.1% to 9%. In the private sector, the mean percent availability of both OBs and LPGs demonstrated slight improvements in 2019, that is, 55.0%–58.3% and 20.3%–32.3%. The adjusted MUPs and MPRs of OBs significantly increased by a median of 4.29% (Wilcoxon test p=0.001, p=0.0001), whereas the adjusted MUPs and MPRs of LPGs increased by a median of 15.7% (p=0.002, p=0.0002). Overall, the affordability of many medicines for common ailments was reduced significantly in 2019. Conclusions: The availability of medicines slightly improved, except in the case of LPGs, which was reduced in the public sector. The implementation of NDPP 2018 led to increase in drug prices, making the standard treatment for some of the most prevalent ailments unaffordable. So verily, the drug pricing policy must be reviewed to ensure access to essential medicines.